STUDY ON THE USE OF INJECTION TECHNIQUES OTHER THAN DIRECT NERVE BLOCK FOR ANAESTHETISING INFERIOR ALVEOLAR NERVE - PRITHI.R,; LOGANATHAN SELVARAJ, (International Journal of Pharma and Bio Sciences, 2016)
The aim of this study was to find out the injection technique that is most commonly used among the dentist to anaesthetize inferior alveolar nerve. Commonly, the classical nerve block and infiltration injection techniques are being used by the dentists. Other than the classical method, specific injection techniques are used for certain reasons among the dentists. This study was done to evaluate which injection method was most and the least preferred by dentist. This study was carried out by an observational assessment of the injection techniques. This study was conducted at among dentists who are practicing in Chennai. About 70 questionnaires were distributed to 70 specialists, questionnaire contained questions related to the type of inferior alveolar nerve block technique the dentists opted for and they were asked to grade them as most commonly, commonly and rarely used. Also they were asked to provide reasons as to why the technique was preferred and reason for non preference. The result of the survey was that, dentist preferred using Direct inferior alveolar nerve block (48%) more commonly and the least preferred technique was the extra oral technique. The study had a sample size of 70. Questionnaire was distributed among the 70 individuals out of the total, direct technique was most commonly preferred by 48% of dentists, indirect technique was followed with 41.4%, Gowgates was preferred by 2.8%, Vazirani Akinosi was preferred by 1.4%. The least preferred injection technique was the extra oral method.